Outcomes and complications of percutaneous device closure in adults with secundum atrial septal defect - Bashir, Faiza; Hameed, Maryam; Hanif, Bashir; Aijaz, Saba (Journal of the Pakistan Medical Association, 2022)
Objectives: To assess immediate outcome and complications of Amplatzer septal occluder percutaneous device for closure of secundum atrial septal defect in adults, and to determine regression in right ventricular size, reduced pulmonary arterial systolic pressure and incidence of device embolization at follow-up. Methods: The single-cohort, ambi-directional, observational study was conducted at the Tabba Heart Institute, Karachi, from January 2013 to July 2018, and comprised patients admitted consecutively for percutaneous atrial septal defect closure. Pre-closure trans-oesophageal echocardiogram was performed in all cases to ensure adequacy of defect margins necessary for device stability. Immediate procedure success and complications were determined by trans-oesophageal echocardiogram, while transthoracic echo was done on follow-up. Data was analysed using SPSS 21. Results: Of the 64 patients, 41(71.9%) were females. The overall mean age was 36.6±14 years. Median size of atrial septal defect was 21mm (interquartile range: 17-26mm). Immediate success was observed in 59(92.2%) patients, and there were 5(8%) acute device embolization events. Small residual atrial septal defect was found in 4(6.3%) cases. On 20-month follow-up, 54(84.4%) patients showed improved symptoms. Repeat transthoracic echo was performed in 39(60.1%) cases, and there were no late embolic events or residual atrial septal defect. Right ventricular size normalized in 34(89.5%) cases, mean pulmonary arterial systolic pressure reduced significantly compared to pre-closure measurement (p<0.001). Conclusion: Percutaneous atrial septal defect closure was found to be safe and effective in adults with secundum atrial septal defect. Timely closure resulted in improved symptoms, right ventricular remodelling and reduced pulmonary arterial systolic Continuous...